2021
DOI: 10.3390/ijms22031042
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog Signaling: Implications in Cancers and Viral Infections

Abstract: The hedgehog (SHH) signaling pathway is primarily involved in embryonic gut development, smooth muscle differentiation, cell proliferation, adult tissue homeostasis, tissue repair following injury, and tissue polarity during the development of vertebrate and invertebrate organisms. GLIoma-associated oncogene homolog (GLI) family of zinc-finger transcription factors and smoothened (SMO) are the signal transducers of the SHH pathway. Both SHH ligand-dependent and independent mechanisms activate GLI proteins. Var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 301 publications
(401 reference statements)
1
31
1
Order By: Relevance
“…Although we did not explore this possibility, our results showed that the expression of GLI2 (only detected in HMC-1.1 and HMC-1.2 cells) is regulated by KIT oncogenic signals, mainly the MEK/ERK1/2 pathway and to some extent the PI3K pathway (Supplementary Figure 1A) suggesting positive feedback loops between KIT and GLI. The increase in GLI2 expression in the rapidly growing neoplastic HMC-1.1 and HMC-1.2 cells (Table 1 and Supplementary Figure 1) is consistent with findings that increased expression of GLI A can lead to transformation (18,19).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although we did not explore this possibility, our results showed that the expression of GLI2 (only detected in HMC-1.1 and HMC-1.2 cells) is regulated by KIT oncogenic signals, mainly the MEK/ERK1/2 pathway and to some extent the PI3K pathway (Supplementary Figure 1A) suggesting positive feedback loops between KIT and GLI. The increase in GLI2 expression in the rapidly growing neoplastic HMC-1.1 and HMC-1.2 cells (Table 1 and Supplementary Figure 1) is consistent with findings that increased expression of GLI A can lead to transformation (18,19).…”
Section: Discussionsupporting
confidence: 88%
“…In the presence of HH ligands, PTCH1 stops the inhibition of SMO, proteolysis of GLI is blocked and thus active, full length GLI activator forms (GLI A ) accumulate and translocate into the nucleus to induce gene transcription. Unlike GLI2 and GLI3, GLI1 is not subject to proteolysis, and its levels are mainly regulated by induction of transcription, which is the reason why GLI1 is used as a reliable reporter of HH activity ( 18 , 19 ). Overall, GLI1 acts exclusively and GLI2 primarily as transcriptional activators (GLI A ), while GLI3 acts as the main transcriptional repressor due to its proteolytic processing ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hedgehog signaling pathway represents a conserved signaling mechanism that plays a critical role in embryogenesis, tissue homeostasis, smooth muscle differentiation, and cell proliferation (Iriana et al, 2021; Jeng et al, 2020; Quaglio et al, 2020). The posttranslational modifications, various transcriptional mechanisms, and nuclear cytoplasmic shuttling regulate the activity of the proteins associated with the hedgehog pathway (Sari et al, 2018).…”
Section: Anticancer Compounds Based On Anthranilic Acid Analoguesmentioning
confidence: 99%
“…In addition to its indispensable role in developmental processes, more than 25% of all cancers require autocrine or paracrine HH signaling as a fundamental supporter of tumor cell growth and survival (Figure 1) (Lum and Beachy, 2004;Iriana et al, 2021). In EBV-positive nasopharyngeal carcinomas (NPC) and EBV-infected epithelial cell lines, the virus can activate the HH signaling pathway through autocrine induction of SHH (Port et al, 2013).…”
Section: Hh Signaling Targeted By Oncogenic Viruses Promotes Tumor Developmentmentioning
confidence: 99%